Impact of Social Labeling on Child Labor in the Indian Carpet Industry - Sayan Chakrabarty; Ulrike Grote (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2007)
Does the labeling of tradable products like carpets which have been produced without child labor contribute to decreased vulnerability of poor households and their children? This paper analyzes which factors determine the probability of a child to work in the carpet industry, and examines the influence of non governmental organizations (NGOs) like Rugmark which are engaged in the social labeling process. Data was obtained from interviews with 417 households in North India. Based on their calorie intake, the households were dissected into two groups, one very poor group below and another one above the subsistence level. The econometric analysis shows that a child living in a very poor household is more likely to work when his/her calorie intake increases (nutritional efficiency wage argument), while the opposite is true for a child from the above-subsistence household group. In addition, it has been found that social labeling has no significant influence on the very poor households. In contrast, at the above-subsistence level, social labeling has a significant positive welfare influence on the households. Furthermore, the occurrence of child labor is more likely for NGOs without monitoring. – – Trägt die Zertifizierung von Produkten, wie z.B. von Teppichen, die ohne Kinderarbeit produziert wurden, zu sinkender Verwundbarkeit armer Haushalte und ihrer Kinder bei? Der Diskussionsbeitrag untersucht die Faktoren, die die Wahrscheinlichkeit bestimmen, dass ein Kind in der Teppichindustrie arbeitet, sowie den Einfluss von Nicht Regierungsorganisationen (NROs) wie Rugmark, die im Bereich der Sozialzertifizierung aktiv sind. Die Daten basieren auf Interviews mit 417 Haushalten in Nordindien. Auf der Basis der Kalorienzufuhr werden die Haushalte in zwei Gruppen aufgeteilt, eine sehr arme Gruppe unterhalb und eine andere oberhalb der Subsistenzgrenze. Die ökonometrische Analyse zeigt, dass die Wahrscheinlichkeit zu arbeiten für ein Kind aus einem sehr armen Haushalt größer ist, wenn seine/ihre Kalorienzufuhr steigt (ernährungsbezogene Effizienzlohntheorie), während das Gegenteil für ein Kind aus einem oberhalb der Subsistenzgrenze lebenden Haushalt zutrifft. Darüber hinaus ist kein signifikanter Einfluss von Sozialzertifizierung auf die sehr armen Haushalte zu finden. Im Gegensatz dazu hat Sozialzertifizierung einen signifikanten Wohlfahrtseffekt auf Haushalte, die sich oberhalb der Subsistenzgrenze befinden. Weiterhin ist die Präsenz von Kinderarbeit wahrscheinlicher, wenn die NROs keine Kontrollen durchführen.
Keywords: I20; C81; D13; O12; J22; 330; Social Labeling; Child Labor; Carpet Industry; India